Necroptosis in CNS diseases: Focus on astrocytes - Mitroshina, Elena V.; Saviuk, Mariia; Vedunova, Maria V. (Frontiers in Aging Neuroscience, 2023)
In the last few years, necroptosis, a recently described type of cell death, has been reported to play an important role in the development of various brain pathologies. Necroptosis is a cell death mechanism that has morphological characteristics similar to necrosis but is mediated by fundamentally different molecular pathways. Necroptosis is initiated by signaling through the interaction of RIP1/RIP3/MLKL proteins (receptor-interacting protein kinase 1/receptor-interacting protein kinase 3/mixed lineage kinase domain-like protein). RIPK1 kinase is usually inactive under physiological conditions. It is activated by stimulation of death receptors (TNFR1, TNFR2, TLR3, and 4, Fas-ligand) by external signals. Phosphorylation of RIPK1 results in the formation of its complex with death receptors. Further, complexes with the second member of the RIP3 and MLKL cascade appear, and the necroptosome is formed. There is enough evidence that necroptosis plays an important role in the pathogenesis of brain ischemia and neurodegenerative diseases. In recent years, a point of view that both neurons and glial cells can play a key role in the development of the central nervous system (CNS) pathologies finds more and more confirmation. Astrocytes play complex roles during neurodegeneration and ischemic brain damage initiating both impair and protective processes. However, the cellular and molecular mechanisms that induce pathogenic activity of astrocytes remain veiled. In this review, we consider these processes in terms of the initiation of necroptosis. On the other hand, it is important to remember that like other types of programmed cell death, necroptosis plays an important role for the organism, as it induces a strong immune response and is involved in the control of cancerogenesis. In this review, we provide an overview of the complex role of necroptosis as an important pathogenetic component of neuronal and astrocyte death in neurodegenerative diseases, epileptogenesis, and ischemic brain damage.